Helper-dependent adenoviral vectors for gene therapy - Brunetti-Pierri, Nicola (Henry Stewart Talks, 2014)
Overview of gene therapy vectors, Helper-Dependent Ad (HDAd) vector, Liver and lung directed gene therapy, Hemophilia B gene therapy, OTC deficiency clinical trial, Balloon occlusion catheter-based delivery of HDAd, HDAd-mediated CF gene therapy, Brain gene therapy, HDAd as genetic vaccine, HDAd and stem cells